EFIKASI DIRI DAN PEMAHAMAN KONSEP IPA DENGAN HASIL BELAJAR ILMU PENGETAHUAN ALAM SISWA SEKOLAH DASAR NEGERI KOTA BENGKULU - Prayuningtyas Angger Wardhani, Prayuningtyas Angger Wardhani (Pascasarjna Universitas Negeri Jakarta, 2015)
Abstract: This study aims to determine: the relationship between self-efficacy and understanding of science concepts to learning outcomes Natural Sciences separately and simultaneously study was conducted in Bengkulu City Elementary School students in 2015 with 32 samples taken using simple random sampling. The technique used to analyze the data is the statistical technique of regression and correlation. The results showed that there was a positive correlation between: (1) efficacy ourselves to learning outcomes Natural Sciences, (2) understanding the concept of Natural Sciences learning outcomes Natural Sciences, (3) self-efficacy and understanding of the concept of Natural Sciences collectively together with the results of study Natural Sciences. Based on the results, it can be concluded understanding of the concept of Sciences Alam memiliki greater contribution to the learning outcomes Natural Sciences compared with self-efficacy. However, self-efficacy and understanding of the concept of Natural Sciences have jointly contributed to the learning outcomes of Natural Sciences.Â Keywords: Self efficacy, understanding of science concepts, learning outcomesÂ Abstrak: Penelitian ini bertujuan untuk mengetahui: hubungan antara efikasi diri dan pemahaman konsep IPA dengan hasil belajar IPA terpisah dan simultan Penelitian dilakukan pada siswa SDN 5 Kota Bengkulu pada tahun 2015 dengan 32 sampel diambil dengan menggunakan simple random sampling. Teknik yang digunakan untuk menganalisis data adalah teknik statistik regresi dan korelasi. Hasil penelitian menunjukkan bahwa ada korelasi positif antara: (1) efikasi diri dengan hasil belajar IPA, (2) pemahaman konsep IPA dengan hasil belajar IPA, (3) efikasi diri dan pemahaman konsep IPA secara bersama-sama dengan hasil Belajar IPA. Kesimpulan dari penelitian ini yaitu pemahaman konsep IPA memiliki kontribusi lebih besar terhadap hasil belajar IPA dibandingkan dengan efikasi diri. Akan tetapi, efikasi diri dan pemahaman konsep IPA memiliki kontribusi secara bersama-sama terhadap hasil belajar IPA.Â Kata kunci: Efikasi diri, pemahaman konsep IPA, hasil belajar IPA